Foliar Fungal Disease Management For Commercial Citrus Groves - Megan M. Dewdney; Jamie D. Burrow (EDIS)
This document is a two-page illustrated identification sheet for commercial management of citrus foliar fungal diseases. It is a minor revision written by Megan M. Dewdney and Jamie D. Burrow, and published by the Plant Pathology Department, March 2019.